Agatha Christie Is The Representative Of The Detective Genre In English Literature (Journal of Pedagogical Inventions and Practices, 2025)
Agatha Christie remains one of the most celebrated authors in the realm of detective fiction. Her mastery in crafting compelling mysteries, along with her memorable characters like Hercule Poirot and Miss Marple, has made her an emblem of the genre. This article explores Christie’s stylistic and structural contributions to detective literature, her narrative techniques, thematic elements, and cultural influence. By analyzing her major works and the development of detective fiction through her lens, the paper aims to underline her enduring legacy as the quintessential representative of the genre in English literature